PENGARUH SUBSTITUSI TEPUNG TERIGU DENGAN TEPUNG TEMPE DAN TEPUNG UBI JALAR KUNING TERHADAP KADAR PROTEIN, KADAR Î’-KAROTEN, DAN MUTU ORGANOLEPTIK ROTI MANIS - Kurniawati, Kurniawati; Ayustaningwarno, Fitriyono (Journal of Nutrition College, 2012)
Background: Increased of high protein and Î²-carotene food consumption is expected may prevent PEM and VAD. Tempeh is a high-protein food stuff, while orange-fleshed sweet potato had high Î²-carotene content. Sweet bread with substitution of tempeh and orange-fleshed sweet potato flours is expected could be an alternative food which had high protein and Î²-carotene content. Objective: Analyze the effect of tempeh and orange-fleshed sweet potato flour substitution on protein and Î²-carotene content, and organoleptic quality of sweet bread. Method: An one factor completely randomized experimental study used 5 level of tempeh and orange-fleshed sweet potato flour substitution, which were 0%:0%, 0%:25%, 10%:15%, 15%:10%, and 25%:0%. Statistical analysis of protein and Î²-carotene content used One Way ANOVA followed by Tukey and Duncan test, while analysis of organoleptic quality used Friedman and Wilcoxon test. Result: Sweet bread with 25% tempeh flour substitution had the highest protein content (14.38%) and 25% orange-fleshed sweet potato flour substitution had the highest Î²-carotene content (0.24 mg/100 g). Substitution of 25% orange-fleshed sweet potato flour and substitution of 10% tempeh -15% orange-fleshed sweet potato flour had significant effect on Î²-carotene content. Tempeh and orange-fleshed sweet potato flour substitution also had significant effect on color, aroma, texture, and taste of sweet bread, but had no but had no significant effect on its protein content. Conclusion: Tempeh flour substitution increased protein content in sweet bread and orange-fleshed sweet potato flour increased its Î²-carotene content. Sweet bread with 10% tempeh-15% orange-fleshed sweet potato flour substitution were recommended.